Persistence of Disparity in Thyroid Cancer Survival After Adjustments for Socioeconomic Status and Access - Nnorom, Siobhan O; Baig, Hana; Akinyemi, Oluwasegun A; Tran, Joseph H; Harris, Jeduthun; Sidhom, Fady; Frederick, Wayne A; Cornwell, 3rd, Edward E; Wilson, Lori L (The American surgeon, 2022)
Thyroid cancer incidence has increased substantially in the past 4 decades, estimated at 3.5% annually. Incidence is highest in white patients, yet black patients have the worst survival. Racial/ethnic differences in presentation and outcomes are hypothesized to be a result of differences in access to care. Analyses delineating the relative contribution of access to racial/ethnic survival disparities are scarce. We aimed to explore the association of delay in access to care and early/increased detection with racial/ethnic disparities in thyroid cancer survival. The Surveillance, Epidemiology, and End Results (SEER) database was queried from 2007 to 2011 for patients with a first primary thyroid cancer diagnosis and up to 5 years of follow-up. Composite scores were generated from county-level variables to capture socioeconomic status and screening habits. Kaplan-Meier analysis and Cox proportional hazards models were utilized for survival analysis. We identified 46,970 patients (67% white, 7% black, 15% Hispanic, 10% Asian or Pacific Islander, and 1% unknown/other). Compared to white patients, black, Hispanic, and Asian or Pacific Islander patients were more likely to present with distant disease (3% vs 5%, 5%, and 6%, respectively; P < .001). After adjusting for sex, age, stage, subtype, tumor size, surgery, radiation, socioeconomics, and screening habits, black patients were the only race/ethnicity found to have increased odds of 5-year mortality compared to white patients (24%, P < .001). Thyroid cancer survival is worst for black patients regardless of socioeconomic status or screening habits. Racial/ethnic disparities in survival are not attributable to early detection alone.